Enhancing savings with technology: an Arduino-based smart money box - Muhamad, Nur Amalina; Othman, Norhalida; Shoib, Mohamad Hilman; Khairul Anuar, Noor Hafizah; Abdul Majid, Masmaria (UiTM Press, 2025)
An Arduino-based Smart Money Box aims to enhance saving habits through the integration of advanced technologies such as Arduino microcontrollers, IoT, and sensor systems. This project addresses the common challenge of establishing and maintaining savings habits by offering real-time feedback and a user-friendly interface to encourage financial management skills. The methodology encompasses simulation, hardware development, and IoT integration to ensure a robust and effective product. The project begins with a comprehensive simulation phase using Proteus 8 Professional for schematic diagrams and PCB designs, and the Arduino IDE for coding. These simulations validate the circuit designs and functionality in a virtual environment, reducing potential errors in subsequent stages. In the hardware development phase, components such as Arduino MEGA microcontrollers, ESP8266 (ESP01) communication modules, a coin acceptor, and a color sensor are assembled and connected on a PCB board, ensuring seamless operation. The system's functionality includes detecting user presence with an IR sensor, processing inserted money or coins with a color sensor and coin acceptor, and updating the savings balance. A buzzer alerts users upon reaching their savings goal. Integration with the Blynk platform facilitates real-time monitoring and tracking of savings via a mobile app, enhancing user engagement and providing immediate feedback.